(untitled) (American Journal of IR 4.0 and Beyond, 2023)
Adequate supply and distribution of quality water to hostel accommodations is one of the basic criteria for rating standard of hostel accommodations in schools. This study examined the major water supply sources available to students in hostel accommodations; assess the factors influencing the water demand, supply, and distribution; determine the quality of water supplied to some selected hostel accommodations in the study area. The study utilizes a mixed approach for data collection. The quantitative approach was conducted using handheld (GPS) to locate the satellite images of the hostels and sources of water within the neighborhood, three samples of water collected were examined critically at Osun State Water Corporation Laboratory. The data collected were queried using ArcMAP/ArcGIS 10.7.1 with the specified NIS(554) Limit 2015. Similarly, the qualitative approach was conducted by distributing 50% of the entire student’s population which represents 110 questionnaires to randomly selected students staying within the study area. Data collected were analysed using percentages and (mean score) ranking. The results show that the major sources of water are wells and boreholes; water supply are insufficient with 55.6% of occupant’s daily supply between 75-125 liters. The critical factors influencing the adequacy and sufficiency of water supplied includes high electricity bills to pump water from wells, insufficient water in wells during dry season causing damage to water pumps, insufficient voltage drop by electricity authority to pump water regularly, insufficient capacity of water pumps to raise water head and poor maintenance of water pumps were ranked high. The study further shows that the physio-chemical analysis of the sources of water is soft and can corrode metal ion, an evidence of both biological and chemical pollution, moderately hard with high settle-able solids, micro-organism and the non-pathogenic which might have influence on the taste and this may serve as indicator that the water is not fit for human consumptions. The study concluded that the sources of water supply needed to undergoes water treatment process before they are supply to hostel accommodations.